2021
DOI: 10.1107/s2052252521009593
|View full text |Cite
|
Sign up to set email alerts
|

Differences in thermal expansion and motion ability for herringbone and face-to-face π-stacked solids

Abstract: A series of aromatic organic molecules functionalized with different halogen atoms (I/ Br), motion-capable groups (olefin, azo or imine) and molecular length were designed and synthesized. The molecules self-assemble in the solid state through halogen bonding and exhibit molecular packing sustained by either herringbone or face-to-face π-stacking, two common motifs in organic semiconductor molecules. Interestingly, dynamic pedal motion is only achieved in solids with herringbone packing. On average, solids wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Here, we synthesized diazo-I as reported and single crystals were grown by slow evaporation from toluene. [17] To investigate the possible convergence at high temperature, we conducted a VT SCXRD experiment by mounting the crystal at 320 K followed by cooling gradually to 270 K in 10 K increments (Table S1-S2). [21] At 320 K, single-crystal analysis revealed diazo-I to lie in the orthorhombic space group Pccn.…”
Section: Structural Transition Of Diazo-imentioning
confidence: 99%
“…Here, we synthesized diazo-I as reported and single crystals were grown by slow evaporation from toluene. [17] To investigate the possible convergence at high temperature, we conducted a VT SCXRD experiment by mounting the crystal at 320 K followed by cooling gradually to 270 K in 10 K increments (Table S1-S2). [21] At 320 K, single-crystal analysis revealed diazo-I to lie in the orthorhombic space group Pccn.…”
Section: Structural Transition Of Diazo-imentioning
confidence: 99%
“…Recently, in an elegant study, the differences in thermal expansion and motion ability were reported for a series of (di)imines, (di)olefins and di(azo) derivatives. Herringbone packing and face-to-face π stacking were studied and key differences in expansion and motion were analysed [54]. In comprehensive melting point analyses, we have shown that the substituent position is more important than the nature of the substituent in a series of 3 × 3 benzamide isomer grids [17][18][19].…”
Section: Enriched Halogen•••halogen Contactsmentioning
confidence: 99%
“…19–21 Single crystals that have undergone reactions in the solid state have been shown to occur under different conditions such as light, 7,22 heat 23–25 or pressure, 26–30 giving way to a variety of reactions with crystal products showing physical properties ranging from the formation of porous molecules 31–33 to mechanical effects. 34–36 These reactions fall in the domain of supramolecular chemistry, as intermolecular bonds between discrete molecules can lead to favourable conditions under which reactions can occur. 2 Topochemistry was first described by Kohlschütter as reactions that can occur in the solid state where the 3D nature of the crystal influences the structures and supramolecular arrangement of molecules in a crystal system, affecting the mechanism of the reaction.…”
Section: Introductionmentioning
confidence: 99%